Symmetry breaking and structure of a mixture of nematic liquid crystals and anisotropic nanoparticles - Krasna, Marjan; Cvetko, Matej; Ambrožič, Milan (Beilstein Journal of Organic Chemistry, 2010)
Orientational ordering of a homogeneous mixture of uniaxial liquid crystalline (LC) molecules and magnetic nanoparticles (NPs) is studied using the Lebwohl–Lasher lattice model. We consider cases where NPs tend to be oriented perpendicularly to LC molecules due to elastic forces. We study domain-type configurations of ensembles, which are quenched from the isotropic phase. We show that for large enough concentrations of NPs the long range uniaxial nematic ordering is replaced by short range order exhibiting strong biaxiality. This suggests that the impact of NPs on orientational ordering of LCs for appropriate concentrations of NPs is reminiscent to the influence of quenched random fields which locally enforce a biaxial ordering.
Keywords: liquid crystals; nanoparticles; orientational order; quenched disorder; symmetry breaking